ASPEK ERGONOMI AKTIVITAS PENANGKAPAN IKAN TUNA PADA KAPAL LONGLINE KM SATELIT, DI MUARA BARU, JAKARTA UTARA - Maria Putri Widhyasari; Vita Rumanti Kurniawati; Budhi Hascaryo Iskandar (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2020)
This research was aiming at analysing ergonomic aspects and identifying potential hazards resulted from fishing activities. Data was collected from a long line fishing vessel MV Satelit. Analysis of ergonomic aspects focused on four major activities namely setting, drifting, hauling and fish handling. The investigation was conducted to examine the suitability of on board working area with fishermen’s movement. The result showed that on board working area was inadequate compared to fishermen’s movement because of limited zones for fishermen (ranged from 1 – 3 m2/ person) without any safety equipment. Based on Job Safety Analysis (JSA), it was revealed that there were 14 potential hazards emerging from fishing activities; 64,29% of them were moderate risk and the rest were trivial risk. However, fishermen have no significant efforts to prevent those hazards. Keywords: : ergonomic, fishing vessel, occupational health and safety, tuna fishing, potential hazards